2014
DOI: 10.1155/2014/945164
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Strengthening in Jimma, Ethiopia: A Mixed-Method Needs Assessment

Abstract: Objective. We assessed how health system priorities matched user expectations and what the needs for antenatal care (ANC) strengthening were for improved maternal health in Jimma, Ethiopia. Methods. A questionnaire survey among all recent mothers in the study area was conducted to study the content of ANC and to identify the predictors of low ANC satisfaction. Further, a qualitative approach was applied to understand perceptions, practices, and policies of ANC. Results. There were no national guidelines for AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
6
11
0
Order By: Relevance
“…However, it requires structural resources and compatible equipment for enabling health providers to make this commitment 32 . It is important to highlight that the high prevalence of resolved demands also contributes to building confidence With regard to privacy, users from all regions mentioned that the lack of an office room that provided privacy decreased the likelihood of achieving USat-PC, confirming the work of Villadsen et al 33 conducted in Ethiopia. This variable had the greatest influence in the North (2.1-fold decrease in USat-PC).…”
Section: Independent Variablessupporting
confidence: 61%
“…However, it requires structural resources and compatible equipment for enabling health providers to make this commitment 32 . It is important to highlight that the high prevalence of resolved demands also contributes to building confidence With regard to privacy, users from all regions mentioned that the lack of an office room that provided privacy decreased the likelihood of achieving USat-PC, confirming the work of Villadsen et al 33 conducted in Ethiopia. This variable had the greatest influence in the North (2.1-fold decrease in USat-PC).…”
Section: Independent Variablessupporting
confidence: 61%
“…The health system in Jimma is dealing with competing needs and priorities with very limited resources. Provision of ANC service has not been given high priority, and the inadequate quality of ANC put women’s trust in the health system at risk [ 31 ]. With this intervention study, we have shown that quality of ANC can be improved in some important aspects with few resources.…”
Section: Discussionmentioning
confidence: 99%
“…An ANC strengthening intervention, the Maternity Study, was launched in the Jimma area and the surrounding urban communities in Southwest Ethiopia, to improve the quality of care and to develop strategies for improved ANC in low-income settings. The setting and prior needs assessment, using a participatory mixed method approach, has been described previously [ 31 ]. In brief, there were no official Ethiopian ANC guidelines in 2008, and the providers in Jimma did not have support to give high priority to ANC.…”
Section: Introductionmentioning
confidence: 99%
“…Villadsen et al 34 and Mendoza Aldana et al 14 also found an association between user satisfaction with the health service and the privacy of the consulting room.…”
Section: Male Female Totalmentioning
confidence: 93%
“…This is an important scientific study because previous studies about user satisfaction with health services were conducted with restricted and localized populations 15,20,27,34,50 and previous studies that include questions related to user satisfaction using PMAQ-AB data were not based on statistical techniques for decision-making.…”
Section: Male Female Totalmentioning
confidence: 99%